Doctrinal analysis on interest for late interim payment for Malaysian construction works contracts - Mohamad Hamdan, Noor Aishah; Ahmad Sarkawi, Azila; Abdullah Habib, Siti Nora Haryati; Othman, Ahmad Azam (Construction Research Institute of Malaysia (CREAM), 2022)
The doctrinal analysis is a legal methodology adopted to understand a particular area of law's principles and practices. In the context where interest is used as a charge for late interim payment, related provisions in the Malaysian construction works contracts are confined by minimal details. Hence, this study aims to identify relevant legal provisions bearing the principles and practices of interest for a late interim payment for the Malaysian construction works contracts using the doctrinal analysis approach. Fifteen cases were selected from the Construction Industry Development Board (CIDB) Law Reports from 2015 until 2018 for the analysis. The doctrinal analysis was conducted in two stages; the first stage was to locate the law sources, and the second stage was to synthesis the findings of the analysis. Through the analysis, seven themes and nineteen sub-themes based on the case judgements and principles related to interest for late interim payment were developed. The findings were subsequently presented to legal experts for validation and comments. This study helps the employer and the contractor be more prudent in forming and treating contractual interest provisions for late interim payment. Also, a better understanding of the legal implications for the said provisions might reduce disputes between the contracting parties.